(untitled) (Fiep Bulletin - online, 2015)
Currently, the World Health Organization (WHO) as the leading cause of preventable death considers smoking worldwide, thus representing one of the most serious public health problems. This research aims to define the profile of tobacco users assisted by a CAPS ad. This is an exploratory, descriptive study with quantitative approach, developed in a CAPS ad in the city of Sousa. The study population has aged 30 to 35 years, mostly 13 (30%) are female, and 33 (75%) have completed elementary school or completed secondary school. When asked about their occupation, 29 (66%) said they work and have a family income 1-2 times the minimum wage. The vast majority of respondents knew and experienced the cigarette even during adolescence. About knowing the risks that smoking causes health started smoking, 28 (64%) said no, 17 (39%) responded to smoke 10-20 cigarettes, 95% believed that smoking status influence on their quality of life and 52% feel rejected by people for being smokers. We conclude that there must be specific and suitable programs for professionals’ workers to deal with this population, being necessary to the awareness on the part of all, considering that this process is long and requires a lot of user.